PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN PUBLIK PADA SISTEM ADMINISTRASI MANUNGGAL SATU ATAP (SAMSAT)KELILING DI UNIT PELAYANAN TERPADU (UPT) DINAS PENDAPATAN PROVINSI SUMATERA UTARA (DISPENDASU) MEDAN UTARA - Emma Novirsari (PERSPEKTIF, 2016)
The government as the provider of the public service has put some efforts to provide excellent service that have been expected by the people. Therefore the government of North Sumatra Province, under North of Medan revenue departement tries to deliver excellent service based on law number 25 year 2009. Hence, one single roof administration system has launched a mobile samsat. However North of Medan revenue departement has observed and received some complaints from the people about the mobile samsat. Generally, this study utilize descriptive qualitative method, by this research, it has attained some findings about the public perception at service in North of Medan revenue departement and how this mobile samsat outreach the expected excellent service based on the law number 25 year 2009.